Correction: Bismuthene nanosheets produced by ionic liquid assisted grinding exfoliation and their use for oxygen reduction reaction. Issue 12 (4th February 2021) - Valappil, Manila Ozhukil; Ganguly, Abhijit; Benson, John; Pillai, Vijayamohanan K.; Alwarappan, Subbiah; Papakonstantinou, Pagona
Abstract : Correction for 'Bismuthene nanosheets produced by ionic liquid assisted grinding exfoliation and their use for oxygen reduction reaction' by Manila Ozhukil Valappil et al., RSC Adv., 2020, 10, 43585–43591, DOI: ; 10.1039/D0RA09763B .